Bandvefsmyndandi berkjungateppa með lungnabólgu : klínísk sérkenni 19 sjúklinga á Íslandi - Ófeigur Tryggvi Þorgeirsson; Steinn Jónsson; Bjarni Agnar Agnarsson; Tryggvi Ásmundsson (Læknafélag Íslands, Læknafélag Reykjavíkur, 2009)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn View/Open The diagnosis of BOOP is based on characteristic changes on lung biopsy in patients with a variety of symptoms and radiographic changes. We studied nineteen patients, ten males and nine females, with biopsy proven BOOP. The most common clinical findings were fever, shortness of breath and non-productive cough for less than eight weeks and inspiratory crackles on auscultation. Laboratory tests often revealed increased erythrocyte sedimentation rate, low grade anemia, moderate increase in white blood cell count and arterial hypoxemia. Irregular alveolar infiltrates were the most common radiographic abnormalities. Open lung biopsy was required in three. Seven patients in our study were considered to have idiopathic or primary BOOP with no identifiable cause. Twelve patients had either an underlying bacterial lung infection, rheumatologic disease or cancer. Thirteen patients received corticosteroid treatment, usually oral prednisolone at an initial dose of 30-60 mg/day, for a variable length of time. Predisolone treatment resulted in recovery with clearing of lung infiltrates in all patients but one, who died of myocardial infarction five days after treatment was begun. However relapses occurred in more than half (57%) of those receiving prednisolone. Relapses usually occurred when the prednisolone doses had been reduced below 15 mg/day, and in patients who had been treated for up to 10 months. Recovery ensued when perdnisolone doses were increased. Four patients recovered after treatment with antibiotics alone. BOOP probably represents a non-specific inflammatory response of the lung to a number of insults. The high proportion of cases with an established underlying disease in our study is unique. Our data also suggest that infection may be the most frequent underlying condition in BOOP. Corticosteroids were effective treatment but relapses were common. A thorough search for an underlying disease is warranted, and if ...